The Urgency of Granting Authority of Judiciary Institutions in Dispute) Effectiveness of Duties and Functions of Civil Service Police as Law Enforcers of Regional Regulations in Ternate City - Fahria Fahria; Muhammad Mufti M Djafar (Khairun Law Journal, 2021)
Ternate City Government in its efforts to make Ternate City a cultured, religious, harmonious, independent, just and environmentally friendly city in accordance with the vision of its government, of course, requires regional apparatus that work effectively and optimally in order to realize the vision of the government. One of the regional apparatus is the Civil Service Police Unit (Satpol PP), which according to the mandate of the laws and regulations has the function and duty of maintaining and carrying out public order and order, including its function of enforcing regional laws in Ternate City. A number of Ternate City regional regulations that are enforced with the aim of creating peace and public order, such as controlling street vendors, squatters, street children and others, of course, must be supported by the effectiveness of the duties and functions of the Satpol PP of the Ternate City Government.In previous studies on the topic of the existence of Satpol PP duties and functions, there has not been a single research study that has questioned the effectiveness of Satpol PP's duties and functions as law enforcer of local regulations, so it can be said that the study to be investigated by this researcher is still a relatively problem. has never been studied by previous researchers. Therefore, it can be said that this research has a novelty and originality side.The general objective of this research is to examine in depth the form of effectiveness of Satpol PP's duties and functions as law enforcer of regional regulations in Ternate City. Meanwhile, the specific objectives of research on this topic are expected to become material for recommendations for local governments and / or stakeholders in fixing and establishing policies (policies) related to the existence of Satpol PP as law enforcers of regional regulations.The method in this study uses a socio-juridical research type with a qualitative research type. Research with the socio-juridical type was used with the reason to identify the form of effectiveness of the Satpol PP's duties and functions as law enforcers of regional regulations in Ternate City. The nature of this research is exploratory in nature which aims to test whether there is a cause and effect relationship between the various problem variables under study. While the approach in this research is to use a conceptual approach (conceptual approach) and a legal instrument approach (statute approach). Data collection techniques in this study were carried out by collecting primary and secondary legal materials in the form of legal policy regulations that regulate the duties and functions of Satpol PP and interviews with informants who are considered relevant to the problems being studied.The research stages in the form of data tracing, data processing, and data completion of research results will be carried out for 6 (six) months in 1 (one) year running period. The mandatory output from the results of this research is in the form of publications in national journals that are ISSN online. Meanwhile, the tentative additional output is in the form of enrichment of teaching materials